2011
DOI: 10.1111/j.1365-2923.2011.03951.x
|View full text |Cite
|
Sign up to set email alerts
|

Using videos to introduce clinical material: effects on empathy

Abstract: defibrillator (AED) correctly. These skills were taught using a combination of lectures and simulation-based small-group sessions. After the presentation of the material by content experts, skills were practised with the experts using airway and CPR manikins, as well as cardiac rhythm generators, defibrillators and AED trainers. Strategies to prevent needlestick injuries during phlebotomy, the correct implementation of universal precautions, and hand washing and hand hygiene were also reviewed, demonstrated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 1 publication
4
17
2
4
Order By: Relevance
“…While some studies have found similar patterns of change in men and women [1,11,26], in one of these studies the effect size of empathy decline was much larger for men [1], and another cross-sectional study found that empathy declined between the third and the fourth-year of medical studies in men but not in women [27]. Two additional studies on the effect of targeted educational program on empathy supported our findings showing a significant increase in empathy in women but not in men [28,29].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While some studies have found similar patterns of change in men and women [1,11,26], in one of these studies the effect size of empathy decline was much larger for men [1], and another cross-sectional study found that empathy declined between the third and the fourth-year of medical studies in men but not in women [27]. Two additional studies on the effect of targeted educational program on empathy supported our findings showing a significant increase in empathy in women but not in men [28,29].…”
Section: Discussionsupporting
confidence: 81%
“…For example, female physicians have been reported to spend more time with their patients [30] and render a more patient-oriented care [31]. It is possible that gender-specific impact of educational programs that we and others [28,29] have observed, were underestimated in previous studies because of small samples, which did not allow to assess such effects. It is also possible that measuring empathy at a single time point would be less sensitive to detect gender differences in empathy as compared to longitudinal studies.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our ndings suggest that gender differences in empathy may exist, and go along with gender differences previously reported in clinical practice [32,33]. It is possible that gender-speci c impact of educational programs that we and others [22,23] have observed were underestimated in previous studies because of small samples which did not allow to assess such effects. It is also possible that measuring empathy at a single time point would be less sensitive to detect gender differences in empathy as compared to longitudinal studies.…”
Section: Discussionsupporting
confidence: 75%
“…Educational interventions have been suggested to prevent empathy decline during medical studies (18)(19)(20)(21)(22)(23). Previous studies have reported on higher empathy in women as compared to men, following such educational interventions [22,23].…”
Section: Introductionmentioning
confidence: 99%